PERBAIKAN KUALITAS KEMASAN DAN LABELISASI PRODUK DALAM OPTIMALISASI STRATEGI PEMASARAN PRODUK ANEKA KERIPIK PADA UMKM SUKARENA – CIOMAS - Maelani, Puspita; Siregar, Dina Khairuna; Amyati, Amyati; Lestari, Dini Martinda (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Sukarena village is a village where there are several business groups/SUMKM with a variety of different products. On the way, business groups in Sukarena face various obstacles and constraints, namely packaging that still uses plastic which is damaged and marketing that is still traditional, namely still sold directly to consumers or entrusted to shops that want to sell their products. To be able to solve the obstacles faced, the service team conducted training by providing knowledge about quality packaging using special food safe plastics and with a long delivery range, and providing product innovation training according to market needs, labeling product logos and online marketing using social media palftorm.